A Retrospective Analysis of the Role of Isolated and Mini Grids in Power System Development - Energy Sector Management Assistance Program (World Bank, Washington, DC, 2017)
This report provides the first historic overview of power system development focused on its evolution from distributed systems to centralized grid systems. It tracks the early development of power systems in several (now) middle- and high-income economies to inform the current drive to deploy new systems and achieve universal access to electricity services. We find that history can provide certain insights to a set of questions faced by today’s energy policy makers. Our review is non-comprehensive, but will hopefully provide fodder for future, more detailed historical research, and shed some light on the complex and fascinating role of mini- or isolated grids in power system development globally. The development of power systems began in several regions of the world in the second half of the 19th century, marking the start of a new era, characterized by disruptive innovation, rapid development and opportunity. Today, electric power systems constitute a fundamental pillar of modern societies and electricity is increasingly recognized as a crucial prerequisite for the achievement of socio-economic prosperity. The development of power systems was affected by multiple factors, some systemically endogenous, such as technical advancements, innovation, entrepreneurial drive and decisions, and some exogenous, such as economic principles, legislative constraints and support, institutional structures, historical contingencies and geographical aspects (Hughes 1983). While numerous paths have been followed over the years there was a common igniting point; small isolated power systems and mini-grids. As technologies improved, demand increased and the policy and regulatory regimes stabilized, larger generators could be built (taking advantage of economies of scale) and electricity could be transmitted over longer distances. These factors resulted in the emergence of centralized utilities (either privately or publicly owned). Typically, mini-grids either became integrated with one another forming the nucleus of a larger centralized system or were absorbed by a larger grid system as it expanded.